PENGARUH MEDIA FLASH CARD TERHADAP HASIL BELAJAR SISWA PADA MATERI KENAMPAKAN ALAM DAN BUATAN DI KELAS III SD NEGERI 105367 SEI JENGGI - Jelita Utami; Yusra Nasution; Lala Jelita Ananda; Husna Parluhutan Tambunan; Khairul Usman (STKIP Subang, 2026)
This study aimed to determine the effect of using flash card media on students' learning outcomes in the topic of Natural and Artificial Features for third-grade students at SD Negeri 105367 Sei Jenggi. This study employed a quantitative approach using a Quasi-Experimental Design with a Nonequivalent Control Group Design. The sample consisted of 36 students, comprising 18 students from Class III A as the experimental class and 18 students from Class III B as the control class at SD Negeri 105367 Sei Jenggi. Data were collected through observation, documentation, and multiple-choice tests. The data were analyzed using validity, reliability, item difficulty, discrimination index, normality, homogeneity, and hypothesis testing through the Independent Samples t-test with the assistance of SPSS software. The results showed that the use of flash card media had a significant effect on the science and social studies (IPAS) learning outcomes of third-grade students at SD Negeri 105367 Sei Jenggi. This was evidenced by the Independent Samples t-test, which produced a significance value (Sig. 2-tailed) of 0.017 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. Therefore, the use of flash card media had a positive effect on students' learning outcomes in the topic of Natural and Artificial Features for third-grade students at SD Negeri 105367 Sei Jenggi.